2021
DOI: 10.3389/fphar.2021.737576
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Forsythiae Fructus From Different Harvest Seasons and Regions by HPLC/NIR Analysis and Anti-inflammatory and Antioxidant Assays

Abstract: Forsythiae Fructus (FF), the dry fruit of Forsythia suspensa (Thunb.) Vahl, has a long history of use in traditional Chinese Medicine for its heat-clearing and detoxifying properties. It possesses clinical therapeutic effects and biological functions showing efficacy in handling different diseases. To investigate the FF differences in Henan, Shanxi, and Shaanxi in August and October, the surface morphology, mid-infrared and near-infrared spectrums, and HPLC were analyzed. Concurrently, the anti-inflammatory an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…For example, it was approved to be used as food for the first time by the local food safety standard of Shanxi Province, China in 2017. Forsythoside A, phillyrin and phillygenol, considered as the main components in Forsythia suspense fruit , have been demonstrated to possess a wide variety of biological activities, such as anti-inflammation, anti-tumor, liver protection, anti-virus [ 4 , 5 ] and anti-oxidation [ 6 , 7 ]. It was reported that contents of forsythoside A and phillyrin in Forsythia suspensa leaves were much higher than those in Forsythia suspensa fruits [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, it was approved to be used as food for the first time by the local food safety standard of Shanxi Province, China in 2017. Forsythoside A, phillyrin and phillygenol, considered as the main components in Forsythia suspense fruit , have been demonstrated to possess a wide variety of biological activities, such as anti-inflammation, anti-tumor, liver protection, anti-virus [ 4 , 5 ] and anti-oxidation [ 6 , 7 ]. It was reported that contents of forsythoside A and phillyrin in Forsythia suspensa leaves were much higher than those in Forsythia suspensa fruits [ 1 ].…”
Section: Introductionmentioning
confidence: 99%